Physical Fitness Analysis of Junior High School Students by Using Indonesian Student Physical Fitness Test (TKPN) - Takia Oktavia Dewi; Muchamad Arif Al Ardha; Hamdani Hamdani; Moh. Fathur Rohman (International Journal of Educational Development, 2024)
Physical fitness is essential for supporting students' daily activities and learning. This study aims to evaluate the physical fitness of students at SMP Negeri 63 Surabaya, specifically those in class VII D and VIII C, and to compare it between male and female students. The research method used was non-experimental with a comparative design, and data analysis was conducted using the Mann Whitney test and Cluster Random Sampling technique. The instrument for measuring physical fitness was the Tes Kebugaran Pelajar Nusantara (TKPN) and a questionnaire based on the TKPN guidelines. The results showed no significant difference in physical fitness between students in class VII D and VIII C, with a p-value of 0.3 (p > 0.05), indicating that their fitness levels were relatively similar. However, there was a significant difference based on gender. Male students had better physical fitness than female students, with a p-value of 0.00 (p < 0.05). Male students were in the "sufficient" category with an average score of 2.05, while female students were in the "poor" category with an average score of 1.2. Overall, both class VII and VIII students were in the "poor" category, with average scores of 1.15 for class VII and 1.25 for class VIII. This indicates the need for improvement in students' physical fitness.